PELATIHAN FOOTWORK BULUTANGKIS 10 REPETISI 2 SET LEBIH BAIK DIBANDINGKAN 5 REPETISI 4 SET UNTUK MENINGKATKAN KEKUATAN OTOT TUNGKAI DAN KELINCAHAN - Astrawan, I Putu; Adiputra, N; Jawi, I Made (Sport and Fitness Journal; Volume 4, No. 2, 2016)
The teaching of basic movements in badminton are now rather directed to the way of walk orfootwork. This research is aiming to learn about the influence of “footwork” training to theimprovement of leg muscles and agility. This experimental research is designed to use therandomized pretest posttest control group design. The research is based on 42 malebadminton students bimpres of the university “UNDIKSHA”, split into 2 groups. Bothgroups were given different training methods, exercising 3 times a week for 6 weeks altogether. Group 1 was given the “footwork” exercise 10 repetitions 2 sets and group twowas given the “footwork” exercise 5 repetitions 4 sets. The leg muscle strength was measuredwith a leg dynamometer and the agility with the zigzag run test. The result of the intergroupt-paired test before and after the training shows group 1 and group 2 (p<0.05). For group 1,the leg muscle strength (kg) and agility (second) was in the average 114.19±33.13 &7.78±0.34 and after the training 183.19±33.56 & 7.28±0.28 with a difference of 69 & 0.50and with an increase 60% and 7%. On the other hand, for group 2 the leg muscle strengthand agility before the training was in the average 113.05±31.30 & 7.74±0.38 and after thetraining 141.10±34.91 & 7.59±0.31 with a difference 28.05 & 0.15 and with an increase of25% and 2%. The increase of the leg muscle strength and agility between both the groupsbefore and after the training was tested with the t-independent test with a significant score of? =0.05. The average leg muscle strength and agility for both the groups before the trainingwas p = 0.90 & 0.78 (p>0.05) and after the training p = 0.00 & 0.00 (p<0.05). The conclusionis training badminton footwork 10 repetition 2 sets better than 5 repetition 4 sets for theimprovement of leg muscle strength and agility.
Keywords: badminton footwork exercise 10 repetitions 2 sets and 5 repetitions 4 sets, leg muscle strength and agility